Winnie-The--Pooh Story Treasure - Milne, A A (Methuen Children books, 1999)
Filled with favorite stories from the first of A. A. Milne and E. H. Shepard's Winnie the Pooh books, this flip book will delight and entertain children and adults alike.
Keywords: Juvenile literature-Fiction